2020
DOI: 10.1007/s11869-020-00888-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in environmental pollutants and air quality during the lockdown in the USA and China: two sides of COVID-19 pandemic

Abstract: The World Health Organization declared the outbreak of the novel coronavirus (COVID-19) as a pandemic on March 11, 2020. Due to the global threat, many countries impose immediate lockdown. The impact of lockdown on the environmental pollutants and climate indicators gained considerable attention in the literature. This study aims to describe the variations in the environmental pollutants (CO, NO 2 , SO 2 , PM 2.5 and PM 10) with and without the lockdown period in the majorly hit states and provinces of the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 39 publications
14
86
1
3
Order By: Relevance
“…Recently, due to COVID-19 crisis, implementation of lockdown restrictions adopted by states and the federal government has resulted in stopping of economic activities such as industrial projects, construction projects, and transportations observing the stagnant phase (Shakoor et al 2020). Consequently, the levels of NO 2 and PM 2.5 particles of air contaminant have declined 64% in major Spanish cities due to COVID-19 precaution measures.…”
Section: Climatology and Weather Conditions In Spainmentioning
confidence: 99%
“…Recently, due to COVID-19 crisis, implementation of lockdown restrictions adopted by states and the federal government has resulted in stopping of economic activities such as industrial projects, construction projects, and transportations observing the stagnant phase (Shakoor et al 2020). Consequently, the levels of NO 2 and PM 2.5 particles of air contaminant have declined 64% in major Spanish cities due to COVID-19 precaution measures.…”
Section: Climatology and Weather Conditions In Spainmentioning
confidence: 99%
“…The rapid spread of this contagious disease includes pneumonia-like symptomatic or asymptomatic manifestations (80% infections) (WHO 2020b). The incubation period of this novel coronavirus is 1-14 days after infection; most commonly, the symptoms start to appear within 5-8 days (Linton et al 2020;Shakoor et al 2020). The infected person could experience mild to severe symptoms mainly including fever (most frequent), cough, shortness of breath.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly reduced environmental pollution was also reported for three cities in central China, comprising 60% lower concentrations of NO 2 and 30% lower concentrations of PM 2.5 particles during the lockdown (Masum and Pal 2020). Another study found 26-49% lower NO 2 concentrations in six cities in China and 29-61% in some states and provinces of the USA comparing with the first quarter of 2019 (Shakoor et al 2020). The same investigation showed a reduction of PM 2.5 concentrations by 7-27% and 11-31%, as well as reduction of PM 10 by 23-79% and 20-25% in China and the USA, respectively.…”
Section: Resultsmentioning
confidence: 78%
“…Most of the studies related to the "lockdown's" influence on air pollution are focused on "classic" pollutants such as NO 2 , CO, SO 2 , PM 2.5 and PM 10 (Anil and Alagha 2020; Shakoor et al 2020;Bilal Bashir et al 2020;Pata 2020). This work intends to focus on the levels of some additional pollutants such as particulate-bound carcinogenic PAHs and particle fraction PM 1 .…”
Section: Introductionmentioning
confidence: 99%